2014
DOI: 10.1542/peds.2013-1615
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Youth Violence Prevention

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Violence is a leading cause of death. The emergency department (ED) can prevent violence through proven interventions; however, these interventions are not broadly implemented. There is little evidence to inform decision-makers of the costs associated with preventing violence. WHAT THIS STUDY ADDS:We report the costs of a brief violence prevention intervention in the ED. We highlight the economic impact of implementation, showing that brief interventions in the ED are an inexpensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[1][2][3][4] Although numerous program models have demonstrated effectiveness in preventing violence, 5 their sustainability hinges on their cost-effectiveness. 6 Hospital-based violence intervention programs (HVIPs) are one promising strategy to prevent interpersonal violence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although numerous program models have demonstrated effectiveness in preventing violence, 5 their sustainability hinges on their cost-effectiveness. 6 Hospital-based violence intervention programs (HVIPs) are one promising strategy to prevent interpersonal violence.…”
Section: Introductionmentioning
confidence: 99%
“…38 A later cost analysis of this trial's intervention estimated the cost ranged from $3.63 to $54.96 per event averted. 39 Our study indicates a continued need to adopt, evaluate, and improve ED-based violence prevention programs.…”
Section: Discussionmentioning
confidence: 82%
“…A recent paper that analyzed the budgetary impact from the payer perspective of implementing two programs comparable to ours, Dating Matters ® and Safe Dates-CDC-developed comprehensive adolescent DV prevention models also aimed at high-risk, urban, minority middle-school youth-found an average cost of $145.40 and $44.81 per student, respectively. (Luo et al,202 ) Using a cost per averted events framework like ours, Sharp et al (2014) evaluated an emergency department (ED)-based program designed to prevent violence among at-risk youth aged 14-18 and found similar results ($3.63-$54.96 per event averted) (Sharp et al, 2014). Dopp et al (2020) showed that a multisite community-based intervention for problematic sexual behaviors (PSBs) in 13-14 year-olds was cost-effective under most scenarios, though the program cost considerably more per participant ($1772 per 1 standard deviation change in PSB) (Dopp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%